Cerebral infarct after bronchial artery embolization - Gao, Feng (BJR Case Rep, 2019)
Bronchial artery embolization is an effective and widely used procedure for controlling hemoptysis. Cerebral infarct after bronchial artery embolization is a rare and severe complication. We report two cases of cerebral infarct complicating bronchial artery embolization, most likely due to errant embolic passage through anastomoses with the ipsilateral subclavian artery.